Complex photonic response reveals three-dimensional self-organization of structural coloured bacterial colonies. Issue 166 (27th May 2020) - Schertel, Lukas; van de Kerkhof, Gea T.; Jacucci, Gianni; Catón, Laura; Ogawa, Yu; Wilts, Bodo D.; Ingham, Colin J.; Vignolini, Silvia; Johansen, Villads E.
Abstract : Vivid colours found in living organisms are often the result of scattering from hierarchical nanostructures, where the interplay between order and disorder in their packing defines visual appearance. In the case of Flavobacterium IR1, the complex arrangement of the cells in polycrystalline three-dimensional lattices is found to be a distinctive fingerprint of colony organization. By combining analytical analysis of the angle-resolved scattering response of in vivo bacterial colonies with numerical modelling, we show that we can assess the inter-cell distance and cell diameter with a resolution below 10 nm, far better than what can be achieved with conventional electron microscopy, suffering from preparation artefacts. Retrieving the role of disorder at different length scales from the salient features in the scattering response enables a precise understanding of the structural organization of the bacteria.